2020
DOI: 10.1016/j.celrep.2020.107523
|View full text |Cite
|
Sign up to set email alerts
|

CytoMAP: A Spatial Analysis Toolbox Reveals Features of Myeloid Cell Organization in Lymphoid Tissues

Abstract: Highlights d CytoMAP is a user-friendly, comprehensive platform for spatial analysis of tissues d Allows quantification of cellular positioning and global tissue structure d Enables exploration of cellular and tissue microenvironment heterogeneity d CytoMAP reveals fundamental features of myeloid cell organization in lymph nodes

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
182
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(196 citation statements)
references
References 69 publications
4
182
0
Order By: Relevance
“…injection in order to keep EMOVI flexible and allow multiplexing of antibodies. Other recently published protocols demonstrated immunolabelling to detect structural components, neurons or vasculature in fixed organs ( 4 , 27 30 ); however, reports describing the detection of immune cells without the use of transgenic animals expressing cell-type specific fluorescent reporters remain rare ( 14 , 21 , 26 ). Our results demonstrated that EMOVI allows multiplexed antibody-based immunolabeling of immune cell populations in whole organs or large tissue pieces after fixation with the advantage of preserving fluorescence over several months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…injection in order to keep EMOVI flexible and allow multiplexing of antibodies. Other recently published protocols demonstrated immunolabelling to detect structural components, neurons or vasculature in fixed organs ( 4 , 27 30 ); however, reports describing the detection of immune cells without the use of transgenic animals expressing cell-type specific fluorescent reporters remain rare ( 14 , 21 , 26 ). Our results demonstrated that EMOVI allows multiplexed antibody-based immunolabeling of immune cell populations in whole organs or large tissue pieces after fixation with the advantage of preserving fluorescence over several months.…”
Section: Discussionmentioning
confidence: 99%
“…However, EMOVI uses washing solution containing low concentrations of Triton-X 100, which further improves tissue penetrance along with de-lipidation ( 14 ). In addition to hyaluronidase treatment, we here often refrained from staining complete organs and instead used around 1mm thick organ slices or pieces to further improve antibody penetration into fixed organs, as has also been recommended by others ( 4 , 14 , 26 , 32 ). We found this type of sectioning crucial especially if aiming at homogenous staining for immune cell populations in organs such as the kidney, liver and heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is performed by an imaging approach that is linked to an analytical pipeline that can process the imaging data through an intuitive and interactive interface, which can provide quantitative outputs. Many such approaches have been described and have advantages and limitations (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). We recently reviewed such approaches and would refer the reader to these previous works (51,52).…”
Section: Available Methods To Assess Immune Cells Within the Kidney Amentioning
confidence: 99%
“…The output from tissue cytometry is expected to further increase, especially with advances in tissue clearing methods that allow mesoscale imaging (35,49,66).…”
Section: Future Outlook Challenges and Conclusionmentioning
confidence: 99%